Epidemic Analysis and Mathematical Modelling of Influenza with Vaccination. - Musiime, Catherine (Kabale University, 2024)
In this study, we discuss a SLIRV model developed by Jonnalagadda & Gaddam (2016) for the transmission of influenza A with vaccination using tools from ordinary differential equations. We show that if the product of the recruitment rate and the ratio of infection rate to mean latent period is less than the product the sums µ + m, µ + m and + a + y; where µ, a, y, m and 1/ware natural death rate, disease-related death rate, recovery rate, vaccination rate and mean latent period, respectively; then the disease-free equilibrium will be locally and globally asymptotically stable, an indication that that disease can be eradicated from the population.